Triple-Negative Breast Cancer Comparison With Canine Mammary Tumors From Light Microscopy to Molecular Pathology - Amirkhani Namagerdi, Asadoor; d’Angelo, Danila; Ciani, Francesca; Iannuzzi, Carmelina Antonella; Napolitano, Francesco; Avallone, Luigi; De Laurentiis, Michelino; Giordano, Antonio (Frontiers in Oncology, 2020)
Abstract Many similar characteristics in human and dog cancers including, spontaneous development, clinical presentation, tumor heterogeneity, disease progression, and response to standard therapies have promoted the approval of this comparative model as an alternative to mice. Breast cancer represents the second most frequent neoplasm in humans after lung cancer. Triple-negative breast cancer (TNBC) constitute around 15% of all cases of breast cancer and do not express estrogen receptor (ER), progesterone receptor (PR) or overexpress human epidermal growth factor receptor 2 (HER2). Breast cancer is the second most frequent neoplasm in sexually intact female dogs after skin cancer. The majority of canine mammary tumors (CMTs) are triple-negative. Due to the high morphological, histologic, and molecular similarities between CMT and human breast cancers (HBC), human biomarkers of HBC are also observable in cases of CMT. Promising breast cancer biomarkers in both humans and canines are cancer-associated stroma (CAS), circulating tumor cells and tumor DNA (ctDNA) ), exosomes and miRNAs, and metabolites.